FORECASTING THE POTENTIAL ROLE OF CASH WAQF AS A ISLAMIC SOCIAL FUND IN ERADICATING POVERTY AND IMPROVING SOCIAL WELFARE: THE USE OF WEIGHTED MOVING AVERAGE METHOD Study at Special Region of Yogyakarta (DIY) - Anggari Marya Kresnowati; Izra Berakon (Global Review of Islamic Economics and Business, 2017)
AbstractThis research investigates the role of cash waqf as a Islamic social fund in eradicating poverty in Special Region of Yogyakarta. Researchers combine both of quantitative and qualitative research methods (triangulation) to increase the perceived quality of research findings. To answer the problems, researchers employe three steps analysis, firstly forecasting with statistical approach using the weighted moving average method; secondly cash waqf simulation; and thirdly researchers propose The New Integrated Model Of Cash Waqf Information System. The results of this study has succesfully answered the progress of cash waqf, the support of stakeholders (government, financial institutions and society) to achieve target of cash waqf. Based on the forecasting moving average method, it can be seen that the collected fund of cash waqf is still very fluctuating in some future period following the trend of cash waqf fund before. In the simulation of cash waqf based on expenditure distribution at DIY , to reach the target of cash waqf in one year, for example in 2018, that is equal to Rp. 684,646,315.33, each household only spend about of Rp. 60,000 to Rp. 80,000 per year. If all Muslim societies especially at DIY have realized the importance of cash waqf, then the potential cash waqf cant be maximized and the flow of cash waqf returns can be distributed to strengthen the social pillars of the region such as poverty, hunger, health and eduaction. Keywords: cash waqf, eradicating poverty, forecasting, simulation, integrated model